1998
DOI: 10.1523/jneurosci.18-11-04353.1998
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Discrimination between Quinine and KCl Is Dependent on Input from the Seventh Cranial Nerve: Implications for the Functional Roles of the Gustatory Nerves in Rats

Abstract: The rat glossopharyngeal nerve (GL), which innervates posterior tongue taste buds, contains several physiologically defined taste fiber types; at least one type is primarily responsive to certain alkaloids (such as quinine), and another is primarily responsive to acids and salts. In contrast, the chorda tympani (CT), which innervates anterior tongue taste buds, does not appear to contain fibers that differentially respond to quinine relative to salts and acids. It was therefore predicted that GL transection sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 77 publications
(76 reference statements)
2
47
0
Order By: Relevance
“…However, the size of electrophysiological responses does not necessarily reveal the relative importance of the taste nerves in taste-mediated behavior. Recent behavioral experiments in rats stress the prominence of the CT over the NG for the bitter taste [26-28]. We have found that mice with bilateral CT cut have a significantly impaired ability to discriminate water from the bitter stimulus denatonium benzoate in two bottle preference (TBP) tests, while mice with bilateral NG cut showed no difference from the sham surgery group (own unpublished observations).…”
Section: Discussionmentioning
confidence: 89%
“…However, the size of electrophysiological responses does not necessarily reveal the relative importance of the taste nerves in taste-mediated behavior. Recent behavioral experiments in rats stress the prominence of the CT over the NG for the bitter taste [26-28]. We have found that mice with bilateral CT cut have a significantly impaired ability to discriminate water from the bitter stimulus denatonium benzoate in two bottle preference (TBP) tests, while mice with bilateral NG cut showed no difference from the sham surgery group (own unpublished observations).…”
Section: Discussionmentioning
confidence: 89%
“…For example, the CT could provide a main cue discriminating NaCl from KCl, or KCl from quinine, while the IX may not play a critical role in the discriminations (Spector and Grill 1992;St John and Spector 1998). In contrast, the IX may be involved in an aversive behavior to toxic foods, because IX transections have been shown to reduce an aversive oromotor response induced by bitter tastants (Travers et al 1987).…”
Section: Implications Of Umami Tastants or Artificial Salivamentioning
confidence: 99%
“…T2R lineage specificity exaggerates the difficulty in identifying T2R, compared to T1R, ligands. CN VII fields, where T1Rs, specific Na + receptors and aversive-electrolyte receptors are located, focus on taste discrimination more than CN IX fields, where T2Rs predominate and reflexes are initiated (Adler et al ., 2000; St John and Spector, 1998; King et al ., 2000). A posterior lingual T2R locus is consistent with CN IX brainstem, projection sites for high-affinity, cycloheximide neural activity (Geran and Travers, 2006); activity that elicits sensations quite unlike quinine (Frank et al ., 2003) as well as protective reflexes (King et al .…”
Section: Species and Inbred Strains Differ In What They Can Tastementioning
confidence: 99%
“…In rodents, CN IX taste-bud containing receptive fields are more involved in ingesting/rejecting via brain-stem motor systems (Travers and Travers, 2005), and CN X receptive fields more involved in protecting the airway (Bradley, 2000) or participating in metabolic pathways in the gut, (Margolskee et al ., 2007) than sensing taste-stimulus quality. Although the CT assumes some GL reflexive functions when cross-wired to posterior fields (King et al ., 2008), it is not yet known that the GL can take over the well-documented CT-mediated discrimination of taste quality (St John and Spector, 1998; Geran et al ., 2002). …”
Section: Taste Quality Codesmentioning
confidence: 99%